Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-68234-9_9
|View full text |Cite
|
Sign up to set email alerts
|

KonneXSALT: First Steps Towards a Semantic Claim Federation Infrastructure

Abstract: Abstract. Dissemination, an important phase of scientific research, can be seen as a communication process between scientists. They expose and support their findings, while discussing claims stated in related scientific publications. However, due to the increasing number of publications, finding a starting point for such a discussion represents a real challenge. At same time, browsing can also be difficult since the communication spans accross multiple publications on the open Web. In this paper we propose a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In this paper, we have presented CORAAL -a unique combination of a publication repository enhanced by semantic links [3] and an engine for automated extraction, integration and exploitation of knowledge contained in the publication texts [2]. We have shown that the tool has promising results in real-world tasks related to biomedical literature search.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we have presented CORAAL -a unique combination of a publication repository enhanced by semantic links [3] and an engine for automated extraction, integration and exploitation of knowledge contained in the publication texts [2]. We have shown that the tool has promising results in real-world tasks related to biomedical literature search.…”
Section: Discussionmentioning
confidence: 99%
“…The publications, their meta-data and full-text were stored and indexed within our KONNEX framework for linked publication data processing [3]. After parsing the input XML article representations, the XML meta-data and structural annotations were quite straightforwardly integrated in the KONNEX RDF repository.…”
Section: Core Technologies and Capabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The tool is based on a recently developed framework for more efficient exploitation of automatically extracted knowledge [17]. We combined the framework with a repository for semantically inter-linked publications [12] in order to provide for comprehensive combination of full-text and knowledgebased search.…”
Section: B Contributions and Structurementioning
confidence: 99%